From the Capitol to the Louvre: The Journey of a Relief of Mithras .......... 311 - Martini, Annarita (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
The history of the Borghese Collection is closely linked to the establishment of the Louvre in Paris and the history of both of them includes a small story about a magnificent relief. The relief represents the god Mithras in the act of killing a Bull; it was found on the Capitoline Hill and testifies to the cult of Mithras in the religious and political center of Ancient Rome. The relief was included in the Borghese Collection and remained attached on the north façade of the main building of Villa Borghese until the sale of the bulk of the collection to Napoleon in 1808. Once in Paris, the relief was placed in the Hall of the Four Seasons of the Musée Napoléon, later to become the Louvre. Now it is still part of the Louvre collection and can be admired in the branch of the Museum in Lens.